Capturing the moment:a snapshot of Mediterranean bryozoan diversity in the early 2023 - ROSSO, ANTONIETTA; MARTINO DI, EMANUELA (Mediterranean Marine Science, 2023)
This paper is an update on the Mediterranean bryozoan diversity since the annotated check-list of Rosso & Di Martino (2016), following the publication of numerous new papers describing new taxa and new species, and adding new records of non-indigenous species. Of the 32 new species described, some replace records of cosmopolitan or widespread species, while some others are the result of the dismantling of species complexes. New records include mainly species and genera previously known from the near Atlantic and subordinately from the Pacific. In addition to replacements, removal of species/genera is also linked to formalized synonymies. These changes also reflect on the composition and representation of families. The updated bryozoan fauna consists of 587 species, 220 genera and 99 families. The different order proportions remain largely unchanged with cheilostomatids (c. 77%) dominating over cyclostomatids (c. 13%) and ctenostomatids (c. 10%). Ten families account for about half of the total species diversity. The new available information is the result of the investigation of habitats and localities previously overlooked, the examination of museum historical collections, as well as a more routinely use of Scanning Electron Microscopy with increasing support from molecular sequencing. Updated biodiversity check-lists represent a unique, simple tool to monitor biodiversity in agreement with the Kunming-Montreal Global Biodiversity Framework adopted by the United Nations.